Genotoxic potential of Carbaryl in the peripheral blood erythrocytes of Anabas testudineus - Bhuniya, S P; Sahoo, S N (Indian Journal of Fisheries, 2011)
Genotoxic potential of Carbaryl in the peripheral blood erythrocytes of Anabas testudineus